Evaluation of the Legislative Process in the Revision of the TNI Law: Transparency, Public Participation, and Constitutionality - Humah, Darsis (PT. Hafasy Dwi Nawasena, 2025)
This study aims to evaluate the legislative process in the revision of the Indonesian National Armed Forces Law (UU TNI) by emphasizing three main aspects: transparency, public participation, and constitutionality. The research method used is a qualitative descriptive case study approach, through in-depth interviews with key informants (members of the House of Representatives, constitutional law academics, civil society activists, TNI representatives, and political observers), analysis of official documents, and non-participant observation. The results of the study indicate that transparency in the discussion of the revision of the TNI Law remains low because meetings are not fully open and public access to the draft bill is limited. Public participation is also not optimal; the space for discussion through Public Hearings is very limited and public aspirations are rarely accommodated in the final draft. From a constitutional aspect, there are articles that potentially conflict with the principle of civilian supremacy and are not fully in line with the 1945 Constitution. Meanwhile, the TNI's perspective tends to encourage the expansion of roles beyond military functions, which has the potential to generate debate in a democratic system. Overall, the revision of the TNI Law is considered not fully democratic and legitimate, because it still faces issues of openness, participation, and compliance with constitutional principles.